THE WHOLISTIC APPROACH TO THE STREET (Sciences & Technologie. D, Sciences de la terre, 2007)
This study is devoted to the examination and the establishment of the street’s multiple dimensions.  It highlights the complexity of the design of the street space and the “responsibility” of the built environment in enhancing the quality of movement, safety and the enjoyment of the pedestrian as well as the motorist. The growing problem of traffic brought the street into focus in the 1970s and since 1980 is becoming a subject of widespread interest.